Clinical characteristics of idiopathic pulmonary fibrosis patients according to their smoking status - Kishaba, Tomoo (J Thorac Dis, 2016)
BACKGROUND: Idiopathic pulmonary fibrosis (IPF) is the most common form of idiopathic interstitial pneumonias (IIPs) of unknown etiology that often affects male, elderly smokers. However, it is sometimes observed in never smokers. This study aimed to clarify the clinical characteristics of IPF in never-smoking patients compared with those in smoking patients. METHODS: We retrospectively reviewed medical records, pulmonary function tests, and chest high-resolution computed tomography (HRCT) scan of never-smoking and smoking IPF patients from July 1, 2008 to June 30, 2013 at our hospital. RESULTS: We identified 32 never-smoking IPF patients and 66 smoking IPF patients. Never-smoking IPF patients developed more acute exacerbation (AE) than smoking IPF patients (50% vs. 18.2%, P<0.0001). The strongest predictor of AE in never-smoking IPF was modified Medical Research Council (mMRC) breathlessness scale [Hazards ratio (HR), 2.84, P=0.006]. The median survival time of never-smoking and smoking were 18.5 (0.1–138) and 26.3 (0.1–98.4) months, P<0.0001, respectively. The Cox proportional hazard model showed that 1-year mMRC breathlessness scale (HR, 3.24, P=0.001) and gender, age, and physiology (GAP) score (HR, 1.59, P=0.029) were strong predictors of mortality in never-smoking IPF patients at our hospital. CONCLUSIONS: In conclusion, never-smoking IPF patients developed AE more often and showed poor prognosis compared with smoking IPF patients. The 1-year mMRC breathlessness scale was an important predictor of mortality at our hospital.